"So that's the way it is for me — always being left out." Acquired Pragmatic Language Impairment and Social Functioning following Traumatic Brain Injury. Issue 3 (21st November 2017) - Douglas, Jacinta M.
Abstract : Our ability to interact appropriately in everyday interpersonal situations is fundamental to successful social integration. Impaired pragmatic competence correlates significantly and substantially with indices of social function across several domains for adults with acquired neurological disorders. In particular, evidence supports the negative impact of pragmatic impairments on the development and maintenance of relationships and community integration more generally. Pragmatic language competence sits in a complex, multifactorial space characterised by interacting associations with cognitive and psychological functions and social and environmental parameters. This complexity is evident in much of the research seeking to unravel the nature and magnitude of interactions between pragmatic language competence and social outcomes in adults with acquired neurological disorders. Over recent years our understanding of the impact of pragmatic impairments on social outcome has benefited substantially from inclusion of the insider's perspective in our research evidence base. Indeed, a methodological inclusion of constructivist paradigms has enabled the development of a rich understanding of the devastating social impact of impaired pragmatic competence. The aim of this paper is to review pragmatic language impairment in the context of traumatic brain injury (TBI) and detail its impact on social functioning from the perspectives of people with TBI and their intimate partners/spouses and friends. With these perspectives as background, the paper concludes with consideration of therapeutic developments and a brief look at a novel intervention designed to reduce the negative impact of pragmatic deficits and improve functional language use following TBI.